Comprehensive analysis of particulate matter, gaseous pollutants, and microbiological contamination in an international chain supermarket - Furst, Leonardo (2024)
Funding Information: The authors are grateful to the Foundation for Science and Technology (FCT, Portugal) for its financial support by national funds FCT/MCTES to CESAM (UIDP/50017/2020, UIDB/50017/2020 and LAP/0094/2020), SusTEC (LA/P/0007/2020), CIMO (UIDB/00690/2020), and to the PhD fellow students Leonardo Furst (https://doi.org/10.54499/2020.08461.BD) and Yago Cipoli (SFRH/BD/04992/2021). H&TRC authors gratefully acknowledge the FCT/MCTES national support through the UIDP/05608/2020 (https://doi.org/10.54499/UIDP/05608/2020) and UIDB/05608/2020 (https://doi.org/10.54499/UIDB/05608/2020). Publisher Copyright: © 2024 The Authors